Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376308
|View full text |Cite
|
Sign up to set email alerts
|

"My Library Has Just Been Obliterated": Producing New Norms of Use Via Software Update

Abstract: Software updates are commonly perceived as tools for fixing flaws and improving functionality. In this paper, we problematise this view by showing how software updates may also be used by vendors to create new norms of use that control user behaviour and reduce their agency. We explore the nature and aftermath of a controversial software update that was released by Spotify in June 2019. By analysing almost 3,500 reactions to this update, we show how it removed and modified several features in ways that severel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Related affordances do not merely invite possession processes, like customisation or display, but enable or constrain processes in a more literal sense (Mardon et al, 2022). A recent illustration is provided by a study of a Spotify software update in June 2019, which showed how platform affordances increased Spotify agency in music choice selection and curation, while limiting users’ capability to create, organise, navigate, and maintain their music libraries (Morreale and Eriksson, 2020).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Related affordances do not merely invite possession processes, like customisation or display, but enable or constrain processes in a more literal sense (Mardon et al, 2022). A recent illustration is provided by a study of a Spotify software update in June 2019, which showed how platform affordances increased Spotify agency in music choice selection and curation, while limiting users’ capability to create, organise, navigate, and maintain their music libraries (Morreale and Eriksson, 2020).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Nevertheless, the study of ethics in music and audio technology is not yet well established, with only a few authors dealing in recent years with the importance of related ethical dilemmas. Researchers in the musical domain have questioned the practices of music streaming services in monitoring users and inducing behaviours, warning about the associated risks [300], [301]. Other authors have examined the ethical dimensions the field of MIR, arguing that such technology is not valueneutral but is influenced by design choices, and so has ethically relevant implications [302].…”
Section: K Ethics Privacy Security and Sustainabilitymentioning
confidence: 99%
“…An ever-increasing corpus of literature in HCI is also proposing that researchers have a responsibility to examine the social and political implications of their work as well as exposing the cultural and ethical consequences of interaction design [4,31,39,47]. Morreale and Eriksson called for HCI researchers to 'critically interrogate the ideologies and norms that are embedded in the software' [39]. This call resonates with Wakkary's recent depiction of artifacts design as an ethico-political practice [50].…”
Section: Social Emancipation and Empowermentmentioning
confidence: 99%